Tangible space: centre for animal assisted therapy. - Verwey, Andri (My University, 2014)
In the Centre for Animal Assisted Therapy, animals act as a therapeutic intervention to improve the well-being of therapy patients. The main medical success of this mode of therapy lies within the tactile experience of touch. This thesis is about discovering an architecture that acts as a platform for interaction between humans and domesticated animals. The human-animal relationship and the architectural spaces it would require to enhance the gathering, are investigated. It explores an architectural language that is inclusive, involved and focused on a worthy spatial perception based on enhanced tactile experiences.
This document is submitted in partial fulfilment for the degree: Master of Architecture [Professional] at the University of the Witwatersrand, Johannesburg, South Africa, in the year 2013.
Keywords: Architecture--Psychological aspects.; Architecture--Human factors.; Architectural design.; Space (Architecture).